2018
DOI: 10.1016/j.eururo.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Abiraterone Acetate and Docetaxel with Androgen Deprivation Therapy in High-risk and Metastatic Hormone-naïve Prostate Cancer: A Systematic Review and Network Meta-analysis

Abstract: ВведениеРак предстательной железы (РПЖ) является наи-более часто выявляемым некожным злокачественным заболеванием в США и Европе и одной из наиболее частых причин онкологической летальности [1]. Не-смотря на эффективность гормональной терапии (ГТ), у всех пациентов с метастатическим процессом рано или поздно отмечается прогрессирование заболева-ния -переход в кастрационно-резистентный РПЖ (КРРПЖ), который ассоциирован с плохим исходом. В 2004 г. по результатам 2 исследований препарат из группы таксанов доцетак… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 91 publications
(77 reference statements)
1
85
0
4
Order By: Relevance
“…More recently, the use of abiraterone acetate and prednisone with ADT in the early castration‐sensitive setting was also shown to improve overall survival in the LATITUDE and STAMPEDE (Arm G) phase III clinical trials. There have been no prospective clinical trials comparing docetaxel and abiraterone in this setting, although some analyses show similar efficacy . However, this does not take into account challenges encountered when delivering chemotherapy in a real‐world setting.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of abiraterone acetate and prednisone with ADT in the early castration‐sensitive setting was also shown to improve overall survival in the LATITUDE and STAMPEDE (Arm G) phase III clinical trials. There have been no prospective clinical trials comparing docetaxel and abiraterone in this setting, although some analyses show similar efficacy . However, this does not take into account challenges encountered when delivering chemotherapy in a real‐world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with best supportive care, enzalutamide had an ICER of $154,300 per QALY . The cost‐effectiveness findings regarding abiraterone are notable; as mentioned above, a meta‐analysis revealed no improvement in OS when abiraterone plus ADT was compared with docetaxel plus ADT …”
Section: Prostate Cancermentioning
confidence: 99%
“…Most recently, data from the STAMPEDE trial and the LATITUDE trial indicated that the addition of abiraterone to ADT was associated with a significantly higher rate of OS and lower treatment failure rate compared with ADT alone. Despite such findings, a recent systematic review and meta‐analysis was performed comparing abiraterone and ADT versus docetaxel and ADT in men with metastatic, hormone‐naive prostate cancer and demonstrated no difference in OS . Trials examining the role of enzalutamide for men with castration‐naive prostate cancer are ongoing (ie, the ARCHES trial) …”
Section: Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations